Pengaruh Pemasaran Digital, Inovasi Produk, dan Pelayanan terhadap Kepuasan Wisatawan di Kota Medan - Ferianto, Maidar; Widodo, Slamet (Jurnal EMT KITA, 2024)
Digital marketing, product innovation, and service play a very important role in increasing tourist satisfaction in the tourism industry. This research aims to explain the crucial role of digital marketing, product innovation, and service in enhancing tourist satisfaction. The research method used in this study is descriptive quantitative research conducted through a literature review on the roles of digital marketing, product innovation, and service in improving satisfaction in the tourism industry. The data obtained were analyzed using descriptive quantitative analysis techniques. The results of the study show that these three variables play a very important role in increasing tourist satisfaction in the tourism industry. Digital marketing, product innovation, and service help the tourism industry achieve optimal performance by creating satisfaction for tourists, and they contribute to achieving a sustainable industry, as they impact the economy, society, and environment